Science Citizens: Bridging Knowledge and Action for All - Ramlan Ramlan; Belay Sitotaw Goshu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2025)
Science education in Ethiopia faces declining interest in hard sciences (biology, chemistry, physics) and fragmented curricula, hindering the development of science-literate citizens amid challenges like energy poverty and food insecurity. Purpose: This study aimed to transform science education by designing an integrated, applied framework that fosters "science citizens" individuals who understand and apply science across high school to PhD levels and engage society, addressing Ethiopia’s urban (Addis Ababa) and rural (Amhara) contexts. Over 18 months, a mixed-methods approach surveys, tests, observations, interviews, focus groups, and artifact analysis evaluated five objectives: interdisciplinary curriculum design, applied projects’ impact, teacher training effectiveness, societal perceptions, and educational continuity. Participants (625) included students, educators, and community members across levels. The curriculum boosted knowledge (19-23%) and engagement (1.0-1.3 points), applied projects enhanced retention (5-15%), and training lifted teacher competency (20-27%). Societal perceptions shifted (30-45% fewer negative views), and a continuity model increased transitions (25-30%) and public engagement (1,500 attendees). Urban areas outperformed rural by 5-10%, reflecting resource gaps. Integrated, applied science education fosters science citizens in Ethiopia, linking education to societal needs energy, agriculture, health despite rural constraints. Scale the model nationally, prioritizing rural labs, teacher training, and public outreach; tracks long-term impacts over 5 years.